2020
DOI: 10.1371/journal.pone.0227785
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for high grain yield and component traits in new plant types of rice

Abstract: A panel of 60 genotypes comprising New Plant Types (NPTs) along with indica , tropical and temperate japonica genotypes was phenotypically evaluated for four seasons in irrigated situation for grain yield per se and component traits. Twenty NPT genotypes were found promising with an average grain yield varying from 5.45 to 8.8 t/ha. A total of 85 SSR markers were used in the study to identify QTLs associated with grain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 85 publications
0
9
0
1
Order By: Relevance
“…Fifty-six of 78 markers exhibited polymorphism (73%), which gave rise to 154 alleles, less than in our previous study 30 . We obtained 128 alleles from 39 polymorphic primers, and more than reported by Donde et al 31 , 154 alleles from 65 polymorphic markers. The present average of 2.7 alleles per locus was lower than that of many other research reports; for example, Noyer et al 32 analyzed 419 rice accessions using 16 SSR markers and reported an average of 9.1 alleles per locus.…”
Section: Discussionmentioning
confidence: 92%
“…Fifty-six of 78 markers exhibited polymorphism (73%), which gave rise to 154 alleles, less than in our previous study 30 . We obtained 128 alleles from 39 polymorphic primers, and more than reported by Donde et al 31 , 154 alleles from 65 polymorphic markers. The present average of 2.7 alleles per locus was lower than that of many other research reports; for example, Noyer et al 32 analyzed 419 rice accessions using 16 SSR markers and reported an average of 9.1 alleles per locus.…”
Section: Discussionmentioning
confidence: 92%
“…Association mapping has shown great promise and power of mapping the complex quantitative traits in plants as compared to traditional bi-parental mapping. Several scientists employed GWAS in the rice population panel for various traits and reported novel QTLs (Suman et al 2020;Haritha et al 2020;Donde et al 2020;Pradhan et al 2019Pradhan et al , 2020Zhang et al 2014Zhang et al , 2019Norton et al 2018;Kadam et al 2018;Juan et al 2018;Prasanth et al 2017;Swamy et al 2017;Xu et al 2016;Lu et al 2015;Zhao et al 2011;Borba et al 2010;Agrama et al 2007). But such study in diverse rice landrace is very meager.…”
Section: Discussionmentioning
confidence: 99%
“…However, linkage mapping approach does not sample the larger pool of genetic variation that may contribute to phenotypic variation within a species. In addition to the bi-parental mapping strategies used in QTL mapping of important agronomic and nutritional traits, GWAS is widely used in the recent times (Suman et al 2020;Haritha et al 2020;Donde et al 2020;Pradhan et al 2019Pradhan et al , 2020Zhang et al 2014Zhang et al , 2019Norton et al 2018;Kadam et al 2018;Juan et al 2018;Prasanth et al 2017;Swamy et al 2017;Xu et al 2016;Lu et al 2015;Zhao et al 2011;Borba et al 2010;Agrama et al 2007). GWAS maximizes the utilization of genetic variation of unrelated individuals in the natural population for large and more representative set of loci without the additional requirement of mapping population development (Kadam et al 2018;Swamy et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher activity of the SBI significantly reduced the rice PH, and, therefore, its application in rice production contributed to breed improved lodging-resistant rice varieties and thus increased yield. Although several studies on associations between markers and the plant height have been conducted in rice [ 10 , 30 , 31 , 32 , 33 ], to date, no report has documented a QTL analysis of the relationships between plant height and its components traits (panicle length and the length of all internodes), using two mapping strategies.…”
Section: Introductionmentioning
confidence: 99%